Regional electroencephalogram (EEG) alpha power and asymmetry in older adults: a study of short-term test–retest reliability - Mathewson, Karen J.; Hashemi, Ali; Sheng, Bruce; Sekuler, Allison B.; Bennett, Patrick J.; Schmidt, Louis A. (Frontiers in Aging Neuroscience, 2015)
Although regional alpha power and asymmetry measures have been widely used as indices of individual differences in emotional processing and affective style in younger populations, there have been relatively few studies that have examined these measures in older adults. Here, we examined the short-term test–retest reliability of resting regional alpha power (7.5 to 12.5 Hz) and asymmetry in a sample of 38 active, community-dwelling older adults (M age = 71.2, SD = 6.5 years). Resting EEG recordings were made before and after a perceptual computer task. Pearson and intra-class correlations indicated acceptable test-retest reliability for alpha power and asymmetry measures in all regions. Interestingly, alpha asymmetry appeared to be less affected by the task than was alpha power. Findings suggest that alpha asymmetry may reflect more enduring, “trait-like” characteristics, while alpha power may reflect more “state-like” processes in older adults.